Unintended detrimental effects of environmental policy: The green paradox and beyond - Edwin van der Werf; Corrado Di Maria (Center for Economic Studies and ifo Institute (CESifo), 2011)
Well-intended policies aimed at reducing greenhouse gas emissions may have unintended undesirable consequences. Recently, a large literature has emerged showing under what conditions this so-called 'Green Paradox' may occur. We review this literature and identify the key mechanisms behind these paradoxical policy outcomes and highlight avenues for future research.
Keywords: F18; Q31; Q41; Q42; Q54; Q58; 330; climate policy; green paradox; non-renewable resources; scarcity; carbon tax; announcement effects; implementation lag; carbon leakage; backstop technology; Umweltpolitik; Klimaschutz; Ankündigungseffekt; Ökonomischer Anreiz